Quality Assessment of Physiotherapy Departments in Tripoli, Libya: A Pilot Study - Amina Basher,; Ahlam Elkheshebi,; Mohammed Ghniya,; Ahmed Nagi,; Zidan Ben Ibrahim,; Khayriyah Hablou, (AlQalam Journal of Medical and Applied Sciences, 2025)
This pilot study aims to assess the extent to which the physiotherapy departments at public hospitals adhere to quality standards. This pilot study was carried out during the period from Jun to August 2021. The assessment form consists of 40 items organized to cover three aspects: Qualifications of the team (10 items), Facility and environmental status (18 items), and Data collection (12 items). The participants' choices in the assessment form were limited to answering within three options only: yes, to some extent, no. The questionnaire was directly distributed to the head of the physiotherapy department in six hospitals located within the city of Tripoli. The findings of this study showed that the physical therapy departments within Tripoli city fulfilled the criteria of quality standards. The facility and environmental status standard, as well as the data collection and analysis, obtained a performance rate of 2.40 on the Likert scale, while the qualifications of the team achieved a 2.19. This findings may provide significant indicators that clarify the future risks that physical therapy departments may encounter, such as, there is no job description for employees in the departments, do not receive annual training, and there is no evidence that they have received annual recertification in cardiopulmonary resuscitation/basic cardiac life support cardiac recovery, lack of concern for conducting a patient/client satisfaction survey and a lack of interest in following up on post-discharge recommendations communicated and documented. The findings also revealed that, while toilets are available in certain physical therapy departments, they are not suitably designed for patients with disabilities. The current study sheds light on evaluating the performance of physiotherapy services, as the physiotherapy departments targeted by the study demonstrated the application of quality standards. Further studies are needed to gain a better insight into the current situation of physiotherapy centers in Libya. The research team recommends providing national accreditation standards for evaluating the quality of performance in physiotherapy centers. In addition, organizing training to improve staff ability to implement quality standards. تهدف هذه الدراسة الاستطلاعية إلى تقييم مدى التزام أقسام العلاج الطبيعي في المستشفيات العامة بمعايير الجودة. وقد أجريت هذه الدراسة خلال الفترة من يونيو إلى أغسطس 2021. يتكون نموذج التقييم من 40 بندًا تغطي ثلاثة محاور رئيسية: مؤهلات الفريق (10 بنود)، حالة المرافق والبيئة (18 بندًا)، وجمع البيانات (12 بندًا). اقتصر اختيار المشاركين في نموذج التقييم على ثلاث خيارات فقط: نعم، إلى حد ما، لا. تم توزيع الاستبيان مباشرة على رؤساء أقسام العلاج الطبيعي في ستة مستشفيات تقع داخل مدينة طرابلس. أظهرت نتائج هذه الدراسة أن أقسام العلاج الطبيعي في مدينة طرابلس استوفت معايير الجودة. حيث حقق معيار حالة المرافق والبيئة، بالإضافة إلى جمع البيانات وتحليلها، معدل أداء بلغ 2.40 على مقياس ليكرت، بينما حقق معيار مؤهلات الفريق معدل أداء بلغ 2.19. قد توفر هذه النتائج مؤشرات مهمة توضح المخاطر المستقبلية التي قد تواجهها أقسام العلاج الطبيعي، مثل عدم وجود وصف وظيفي للموظفين، وعدم تلقيهم تدريبًا سنويًا، بالإضافة إلى عدم وجود دليل على حصولهم على تجديد سنوي لشهادة الإنعاش القلبي الرئوي/دعم الحياة القلبي الأساسي. كما كشفت الدراسة عن نقص الاهتمام بإجراء استبيانات لقياس رضا المرضى، وعدم الاهتمام بمتابعة التوصيات المقدمة بعد خروج المرضى من المستشفى وتوثيقها. كما أظهرت النتائج أنه وعلى الرغم من توفر دورات المياه في بعض أقسام العلاج الطبيعي، إلا أنها غير مصممة بشكل مناسب للمرضى ذوي الإعاقة. تسلط هذه الدراسة الضوء على تقييم أداء خدمات العلاج الطبيعي، حيث أظهرت أقسام العلاج الطبيعي التي استهدفتها الدراسة التزاماً بمعايير الجودة. ومع ذلك، هناك حاجة إلى مزيد من الدراسات لاكتساب رؤية أعمق حول الوضع الحالي لمراكز العلاج الطبيعي في ليبيا. ويوصي فريق البحث بوضع معايير اعتماد وطنية لتقييم جودة الأداء في مراكز العلاج الطبيعي، بالإضافة إلى تنظيم برامج تدريبية لتحسين قدرة الكوادر على تنفيذ معايير الجودة